Digital Pedagogy: An effective Model for 21st Century Education - Dhakal, Bed Prasad (Academic Journal of Mathematics Education, 2023)
Prior to COVID-19, very few teachers had introduced technology to deliver teaching learning activities. While COVID-19 created a sudden and unexpected situation, it has motivated large number of teachers to utilize digital tools in curriculum, pedagogy, and assessment. With this emerging context of technology use for 21st century education, student have already started to learn from their personal handheld devices, but teachers are navigating unparalleled challenges to manage students learning and classroom pedagogical skills using digital tools. This gap is seen between technology innovation, race of todays’ learners, and pace of pedagogy governance. In this context, this paper articulates a framework for teacher to ensure effective use of Digital Pedagogy (DP) for 21st century education through designed based action research carried out to master’s students of mathematics education at Central Department of Mathematics Education (CDED), TU during the academic year 2017 (Aug-Dec). The study participants were 126 third semester students taking a course "Differential Geometry". The used tools are DP model, mathematics achievement test (MAT) and semi-structure interview guideline. Based on the analysis of data, it is found that DP is effective model to adopt modern student-centered pedagogical practices, where the focus is on students’ learning and emergent activity, rather than teacher’s lectures and teacher-led activities.